Can flare be predicted in DMARD treated RA patients in remission, and is it important? A cohort study. Issue 8 (31st January 2012) - Saleem, Benazir; Brown, Andrew K; Quinn, Mark; Karim, Zunaid; Hensor, Elizabeth M A; Conaghan, Philip; Peterfy, Charles; Wakefield, Richard J; Emery, Paul
Abstract : Objectives: The treatment target for patients with rheumatoid arthritis (RA) is remission. Imaging techniques and remission criteria may identify patients at risk of flare and associated consequences. This study aimed to determine the clinical, functional and imaging associations of disease flare in patients with RA in remission and any effect on long-term outcomes. Methods: RA patients in clinical remission as determined by their treating rheumatologist were assessed using clinical, remission criteria, imaging, functional and quality of life measures over 12 months. Flare was defined as any increase in disease activity requiring a change in therapy. Results: 26% of patients (24/93) in remission experienced a flare within 1 year. Fulfilment of remission criteria was not associated with a reduced likelihood of flare. Increased baseline ultrasound power Doppler (PD) activity (unadjusted OR (95% CI) 4.08 (1.26 to 13.19), p=0.014) and functional disability (Health Assessment Questionnaire Disability Index (HAQ-DI) per 0.1 unit1.27 (1.07 to 1.52), p=0.006) were independently associated with risk of flare. Patients who had a flare had significantly worse long-term clinical (Disease Activity Score 28; mean (95% CI) 2.90 (2.55 to 3.24) vs 2.26 (2.06 to 2.46), p=0.002) and functional outcomes (HAQ-DI; 0.412 (0.344 to 0.481) vs 0.322 (0.282 to 0.362), p=0.029) at 12 months compared with patients in sustained remission. Conclusion: The presence of PD activity was the most accurate determinant of flare in RA patients in remission. Flare was associated with worse clinical and functional outcomes. These results suggest ultrasound could form an important part of remission assessment in RA.